Choosing between Targeted Therapies for Rheumatoid Arthritis Patients: The Oncology Perspective - Bongartz, Tim (Current Rheumatology Reviews, 2011)
Over the last decade, protein-based pharmaceuticals, so called “biologics”, have greatly expanded the therapeutic armamentarium for the treatment of rheumatoid arthritis (RA). Because antiinflammatory therapies with biologics do have multifaceted interactions with pathways involved in carcinogenesis, concerns have been raised that these agents may induce or accelerate malignant growth. Safety analyses based on clinical trial data and observational studies are facing major methodological challenges inherent to the attempt of addressing a possible impact of biologic therapies on a sparse and multifactorial event such as cancer. The expanding palette of approved biologics for the treatment of RA does add additional complexity and raises the issue of how different biologic therapies may compare to each other in terms of their oncogenic effects. This question is of particular importance in patients who have a history of previous malignancy or who develop a cancer while receiving a biologic agent. This review summarizes the published data relevant to a possible link between different biologic agents and malignancies. It explores the question of whether there is enough evidence to support preference of a particular biologic agent over another in different clinical scenarios.
Keywords: malignancy